Assessment of Mesozoic and Upper Paleozoic source rocks in the South Yellow Sea Basin based on the continuous borehole CSDP-2. (March 2019) - Cai, Laixing; Xiao, Guolin; Guo, Xingwei; Wang, Jiao; Wu, Zhiqiang; Li, Baogang
Abstract: Being lack of core data and measured data, although the marine oil & gas exploration in the South Yellow Sea Basin has been going on for 57 years, no commercial hydrocarbon reservoirs have been found so far. The quantitative source rocks evaluation based on geochemical data and fluid inclusions containing hydrocarbon benefits from the completion of borehole CSDP-2 in 2016, a continuous coring well of the Chinese Continental Shelf Drilling Program (CSDP), which indicates that the marine origin oil-gas exploration in the South Yellow Sea Basin enters into a new stage. As revealed by the well CSDP-2, three sets of effective hydrocarbon source rocks in the Mesozoic and Upper Paleozoic have been identified, which are distributed in the Lower Triassic Qinglong Formation (T1 q ), Upper Permian Longtan-Dalong Formation (P3 l-d ) and Middle Permian Gufeng-Qixia Formation (P2 g-q ) respectively. Among them, organic-rich source rocks mainly concentrate in the lower part of the P3 l-d and the middle & upper part of the P2 g-q, and the P3 d mudstone also works as good source rock. The P3 l-d mudstone with high organic abundance is the chief source rock in the South Yellow Sea Basin, whose maximum hydrocarbon-generating intensity may reaches up to 795.09 × 10 4 t/km 2 and hydrocarbon-expulsing intensity remains at the level of 165.03 × 10 4 t/km 2 . A noteworthy feature of the P2 g-q source rocks is the strong vertical heterogeneity, with the hydrocarbon-expulsing intensity of the upper part being 34.14 × 10 4 t/km 2 while that of the lower part being 18.07 × 10 4 t/km 2 . In contrast, the organic abundance of argillaceous limestone in the T1 q is mainly poor to medium and its hydrocarbon-expulsing intensity is the weakest one in the three sets of hydrocarbon source rocks, only about 12.7 × 10 4 t/km 2 . Taking into consideration the joint influence of depositional environment, organic matter parent source and biological productivity, the overall quality of source rocks in the South Yellow Sea Basin is at the similar level to the Lower Yangtze Subei Basin, but lower than that of the Upper Yangtze Sichuan Basin. The most significant oil & gas information is that multiple direct oil indications and high value abnormalities of gas logging have been discovered in the well CSDP-2. Moreover, the Mesozoic and Upper Paleozoic marine strata in the South Yellow Sea Basin have experienced three hydrocarbon charging stages, indicating a broad prospect of marine oil & gas exploration. Highlights: Three sets of source rocks and a new exploration prospect of marine oil & gas were found in the South Yellow Sea Basin, China. In the three vertical source rocks, hydrocarbon-expulsing intensity of the P3 l-d mudstone is the largest. The qualities of source rocks in the South Yellow Sea Basin is at the similar level to the Lower Yangtze Subei Basin, but lower than that of the Upper Yangtze Sichuan Basin.